Clinical outcome measures and return-to-sport timing in adolescent athletes after anterior cruciate ligament reconstruction - Burland, J. P.; Kostyun, R. O.; Kostyun, K. J.; Solomito, M.; Nissen, C.; Milewski, M. D. (Journal of Athletic Training, 2018)
Objective: To investigate the relationship between self-reported and functional outcome measures on return-to-play timing in an adolescent population, in athletes who returned and those who did not return to sport, and to identify a cutoff value for isometric quadriceps strength that could serve as a clinical target for maximizing the odds of returning to play after ACLR.